Implementation of STEM Education in Schools: A Bibliometric Analysis (2003-2024) - Ghany Desti Laksita; Widowati Pusporini; Era Mutiara; Zafrullah Zafrullah; Zamzami Zamzami (Jurnal Penelitian Pendidikan IPA, 2024)
STEM education offers significant benefits, including improving students' ability to solve problems, think critically and innovate. It not only prepares students to enter the workforce, but also facilitates their engagement in society at large. The main objective of this study is to provide a comprehensive bibliometric analysis of STEM education research from 2003 to 2024. It will identify the most prolific affiliations, sources, authors and documents as well as key research themes and trends in STEM education. This research is a bibliometric study with a PRISMA design that will help the authors to map the Scopus database. From the results of the above analysis, it can be concluded that the implementation of STEM education in schools shows a significantly increasing trend over the period 2003-2024, with a surge of publications starting in 2018 and peaking in 2020 and 2021 with 18 publications per year each. Asia was the most productive continent, with 47.52% of articles published by affiliates from this region, dominated by seven affiliates from countries such as Vietnam, Hong Kong, Turkey and Malaysia. Europe and Australia also showed high productivity with significant contributions from universities in countries such as Germany, Ireland, Greece and Australia